1985
DOI: 10.1007/bf01253053
|View full text |Cite
|
Sign up to set email alerts
|

Fenfluramine stimulation of serum cortisol in patients with major affective disorders and healthy controls: further evidence for a central serotonergic action of lithium in man

Abstract: In order to investigate the influence of lithium long-term medication on serotonergic neurotransmission, fenfluramine stimulation (FFS) was used for the assessment of hormonal effects under serotonergic control. The cortisol plasma concentration following FFS was examined between 8 a.m. and 1 p.m. in 11 manic-depressive subjects under lithium prophylaxis and in 8 untreated euthymic patients. In addition, 11 healthy subjects with FFS, and 12 other subjects without FFS were investigated. The basal cortisol conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(27 citation statements)
references
References 49 publications
(41 reference statements)
2
25
0
Order By: Relevance
“…These findings consolidate earlier reports [Muhlbauer and Muller-Oerlinghausen, 1985;Asnis et al" 1988;Lopez-Ibor et al, 1988], Furthermore, we found that the secretion of the related pituitary hormones -ACTH and P-endorphins -did not differ between major and minor depressives. These results are at variance with the find ings of Meltzer et al [1984] and Maes et al [1987Maes et al [ , 1989d who found a hyperresponsivity of ACTH and/or cortisol after loading with 5-hydroxytryptophan in major depressives.…”
Section: Discussionsupporting
confidence: 81%
“…These findings consolidate earlier reports [Muhlbauer and Muller-Oerlinghausen, 1985;Asnis et al" 1988;Lopez-Ibor et al, 1988], Furthermore, we found that the secretion of the related pituitary hormones -ACTH and P-endorphins -did not differ between major and minor depressives. These results are at variance with the find ings of Meltzer et al [1984] and Maes et al [1987Maes et al [ , 1989d who found a hyperresponsivity of ACTH and/or cortisol after loading with 5-hydroxytryptophan in major depressives.…”
Section: Discussionsupporting
confidence: 81%
“…The reported increases in plasma cortisol response to fenfluramine following lithium treatment (Mannel et al, 1997; Muhlbauer and Muller-Oerlinghausen, 1985) and in the L-5-HTTP-induced cortisol response following divalproex treatment (Maes et al, 1997) in BD patients appear particularly compatible with enhanced post-synaptic 5-HT 1A receptor function. In the case of lithium, the increase in post-synaptic 5-HT 1A receptor BP P fits within the context of increased serotonin release more generally, implying that these changes would interact to enhance post-synaptic 5-HT 1A receptor neurotransmission.…”
Section: Discussionmentioning
confidence: 97%
“…. hypo thesis that lithium might possibly act by a serotonergic mechanism, it is planned to examine the central serotonergic acitivty by use of the fenfluramine test (13) in the same subjects where also the ASF to auditory stimuli is assessed. Surprisingly, the latencies of the NI and P2 components were significantly shorter in the responders than in the nonresponders.…”
Section: Resultsmentioning
confidence: 99%